Misappropriation of assets in local authorities: A challenge to good governance - Ab Majid, Rozaiha; Mohamed, Nafsiah; Haron, Rosmawati; Omar, Nor Bahiyah; Jomitin, Betsy (Elsevier Ltd., 2014)
Misappropriation of assets is indeed becoming a major concern in the public sector.In this paper, we will attempt to frame the results survey on assets misappropriation that might occur in two city councils.It is found that the incidence of misappropriation of assets occurs when employees used the official vehicles, computers, and facilities for personal interest.Even though the impact might not significant, yet, if it is left untreated, the symptom will become an incurable disease.As a result, the trivial instalments will create tremendous impact on the financial waste due to the unnecessary expenditure incurred.